2022
DOI: 10.3390/healthcare11010042
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Evaluation and Prescription in Older Adults

Abstract: The over-65 age group is growing faster than other age groups worldwide [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In fact, beneficial effects have been found on the capacity to balance [45,51] and on the subsequent risk of falls [52], as well as on the contrast of pathologies such as osteoporosis [53,54] and sarcopenia [55,56]. However, as reported by Furtado et al (2023), it is necessary to implement new methodologies and intervention strategies to increase the involvement of the elderly population and increase adherence to physical activity, minimizing barriers to participation [14]. Indeed, different types of exercise settings exist and among these, also due to the COVID-19 pandemic, outdoor exercise and telecoaching are increasingly implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, beneficial effects have been found on the capacity to balance [45,51] and on the subsequent risk of falls [52], as well as on the contrast of pathologies such as osteoporosis [53,54] and sarcopenia [55,56]. However, as reported by Furtado et al (2023), it is necessary to implement new methodologies and intervention strategies to increase the involvement of the elderly population and increase adherence to physical activity, minimizing barriers to participation [14]. Indeed, different types of exercise settings exist and among these, also due to the COVID-19 pandemic, outdoor exercise and telecoaching are increasingly implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Although healthy aging is a multifactorial phenomenon, regular physical activity and exercise can contribute to preserve the physical and mental components, consequently improving quality of life [13]. The literature suggests that it is necessary to identify effective methods to increase engagement and maintain high training adherence in this population [14,15]. Several studies have demonstrated the fundamental role played by physical activity and exercise in combating heart disease, diabetes, osteoporosis, the risk of falls, and other common deficits that affect the elderly population [16,17].…”
Section: Introductionmentioning
confidence: 99%